2010
DOI: 10.1073/pnas.1011098108
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional role of a transcribed noncoding RNA with an ultraconserved element in hepatocellular carcinoma

Abstract: Although expression of non-protein-coding RNA (ncRNA) can be altered in human cancers, their functional relevance is unknown. Ultraconserved regions are noncoding genomic segments that are 100% conserved across humans, mice, and rats. Conservation of gene sequences across species may indicate an essential functional role, and therefore we evaluated the expression of ultraconserved RNAs (ucRNA) in hepatocellular cancer (HCC). The global expression of ucRNAs was analyzed with a custom microarray. Expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
165
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(170 citation statements)
references
References 42 publications
(46 reference statements)
2
165
1
2
Order By: Relevance
“…A growing number of ncRNAs are being considered as regulators of various cellular processes (Mercer and Mattick 2013), whereas relatively few ncRNAs are reported to be associated with hepatocarcinogenesis (Braconi et al 2011;Spizzo et al 2012). We have established a comprehensive map of promoters for ncRNAs actively transcribed in a large set of human HCCs as well as in the Mdr2 KO mouse model of HCC using CAGE.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of ncRNAs are being considered as regulators of various cellular processes (Mercer and Mattick 2013), whereas relatively few ncRNAs are reported to be associated with hepatocarcinogenesis (Braconi et al 2011;Spizzo et al 2012). We have established a comprehensive map of promoters for ncRNAs actively transcribed in a large set of human HCCs as well as in the Mdr2 KO mouse model of HCC using CAGE.…”
Section: Discussionmentioning
confidence: 99%
“…According to another study, levels of the lncRNA uc.338 are elevated in HCC cells and may be a promising marker for this type of cancer. Aberrant expression of its transcript, TUC338, is found in transformed hepatocytes, and its functional role in modulating growth may make it a desirable therapeutic target for selected HCC cases (Braconi et al, 2011). Collectively, these studies lead us to propose that lncRNAs may serve as key regulatory hubs in HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…The siRNA sequences (5'-3') were as follows: siRNA-1, UGA CAG CCC UGG AGA CUG A; siRNA-2, CCA CAG GAC AGG UAC AGC A (8). HeLa and C33A cells were transfected with 60 nM TUC338 siRNA (8) or 0 nM siRNA as the negative control (NC) by Lipofectamine ® 2000 (Invitrogen Life Technologies; Thermo Fisher Scientific, Inc.) for 48 h prior to further experiments, according to the manufacturer's instructions. The transfected cells were incubated at 37˚C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Braconi et al (8) demonstrated that TUC338 is markedly overexpressed in hepatocellular cancer (HCC) cell lines and tissue, and it promotes tumor cellular proliferation and modulates progression through regulation of the cell cycle. However, the expression level and biological role of TUC338 in CC remains unclear.…”
Section: Introductionmentioning
confidence: 99%